Design and implementation of a smart monitoring system for water quality of fish farms - Nahla Abdul Jalil Salih; Ihsan Jabbar Hasan; Nadhir Ibrahim Abdulkhaleq (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Fish farms are one of the most important sources of profitability for farmers. Therefore, these farms must be cared for and monitored continuously. the paper discuss  a smart system monitoring in a new way that we designed to monitor the quality and temperature of the fish pond’s water. This system has been designed and implemented to measure and monitor the pH and the temperature value of the fish pond’s water in real time. The system is divided into a measuring and monitoring part. The measuring part uses Arduino UNO as a microcontroller to measure the pH and temperature from the sensors. The data is then sent to the second part by Bluetooth. The second part (the monitoring part), is a new  application for smartphone  designed by ‘MIT App Inventor 2’, which monitors the status of the full system. The ‘MIT App Inventor 2’ is a google software (opensource) that enables you to easily build an Android application. The main advantage of this system is its ability to monitor the fish farms from long distances, with low cost and high reliability.